COMPRESSIVE STRENGTH AND WATER ABSORPTION OF SCC MORTAR PAVING BLOCKS BASED ON LOW-VOLUME FLY ASH MODIFIED WITH CORN COB ASH - Harsan Ingot Hasudungan; Muh. Samsunar Fajar (PT. Radja Intercontinental Publishing, 2026)
This experimental study investigates the compressive strength, water absorption, and workability of self-compacting concrete (SCC) mortar paving blocks incorporating low-volume fly ash (LVFA) and corn cob ash (CCA). Fly ash and corn cob ash were used at proportions of 0%, 5%, 7.5%, and 10% of the total cement mass. Compressive strength was evaluated at 7, 14, and 28 days, while water absorption and slump-flow tests were also conducted. The results indicate that increasing fly ash content improves slump-flow and enhances the flowability of fresh SCC mortar. In contrast, increasing corn cob ash reduces slump-flow because its fine, absorptive particles increase water demand. Considering mechanical performance and workability, the optimum mixture contained 10% fly ash and 5% corn cob ash. It achieved compressive strengths of approximately 29.45 MPa at 7 days, 34.65 MPa at 14 days, and 36.57 MPa at 28 days. Water absorption decreased from 5.21% at 7 days to 4.20% at 14 days and 3.00% at 28 days. The results demonstrate the potential of combining LVFA and corn cob ash in durable SCC mortar paving blocks while supporting the beneficial use of industrial and agricultural waste.